The Study Effect of Addition Magnesia (MgO) on Some Physical and Mechanical Properties for Alumina - Watan, A.W.; Hassin, S. K. Abd-; Harrbi, K. H . (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A reseach is carried out by using Alumina material type Î±-Al2O3 which has partical size 63Î¼m doped with different percentage weight of MgO (0.1%,0.3%and0.5%) and by using dry press method to prepare the samples ,A force press 50KN used and sintering to 1500oC with soaking time of 6 hours. The physical properties were studied such as "Bulk density ,Porosity and water absorption "also the mechanical properties such as (hardness,compressive strength ), the result shows that the best ratio of maginsa(MgO) added to Alumina (Al2O3)is 0.5%and this worked to improve Physical and mechanical properties .